[\<- 1.7](1.7.md) --- # 1.8 Proof Methods p1 ## Proof by Cases - Ex. Prove that `n^2 + 5n + 8` is even for all n∈ℤ. - case 1 (n is odd): Let `n` be odd. Ǝk∈ℤ s.t. `n=2k+1`. Then `n^2 + 5n + 8` = `(2k+1)^2 + 5(2k+1) + 8` = `4k^2 + 4k + 1 + 10k + 5 + 8` = `4k^2 + 14k + 14` = `2(2k^2 + 7k + 7)` which is **even** since (2k^2 + 7k + 7)∈ℤ. - case 2 (n is even): Let `n` be even. Ǝk∈ℤ s.t. `n=2k`. Then `n^2 + 5n + 8` = `(2k)^2 + 5(2k) + 8` = `4k^2 + 10k + 8` = `2(2k^2 + 5k + 4)` which is **even** since `2k^2 + 5k + 4` is an integer. - ∴ `n^2 + 5n + 8` is even for all n∈ℤ - ∴ means "therefore" --- Sometimes, the proofs of multiple cases are essentially the same, so we will say "without loss of generality" (or **WLOG**) and just show the argument for one of the similar cases and omit the others - Ex. Let max(x,y) be the maximum of `x` and `y`. For example, max(7.2, 11.4) = 11.4 and max(-3,-3) = -3. Similarly define min(x,y) as the minimum of `x` and `y`. - Prove `max(a,b) - min(a,b) = |b-a|` for all a,b∈ℝ. - We could do cases: - Case 1: `a>=b` - Case 2: `b>=a` - Notice the problem is **symmetric** in a,b (`max(b,a)-min(b,a) = max(a,b)-min(a,b)`) - `a` and `b` are interchangeable Proof: Let a,b∈ℝ. without loss of generality, assume `a>=b`. Then, LHS (left hand side) = `max(a,b)-min(a,b)` = `a-b`. Note `|x| = x` for `x>0` and `|x| = -x` if `x<=0`. RHS (right hand side) = `|b-a|` = `-(b-a)` = `a-b`. ∴ LHS = RHS as desired. ▣ - We don't need to consider the other case since it would have been identical --- - To prove `p<->q`, we must show 1. `p->q` 2. `q->p` - Ex. Let n∈ℤ. Prove `n` is odd iff `n^2` is odd. Proof: - (=>)(implication arrow) "If `n` is odd, then `n^2` is odd" - We already proved this in [1.7](1.7.md) - (<=)(implication arrow; reverse direction) "If `n^2` is odd, then `n` is odd" - **Direct Proof**: - Ǝk∈ℤ s.t. `n^2 = 2k+1` - `n = ±sqrt(2k+1)` - not sure if `±sqrt(2k+1)` is an integer :( - **Contraposition**: "If `n` is even, then `n^2` is even` - Let `n` be even. Ǝk∈ℤ s.t. `n = 2k`. - Then, `n^2 = (2k)^2 = 4k^2 = 2(2k^2)` which is even since `(2k)^2`∈ℤ - ∴ `n` is odd iff `n^2` is odd. ▣ - Definition: A **theorem** is a mathematical statement that can be shown/proven to be true - Definition: A **proposition** is a "less important" **theorem** - Definition: A **corollary** is a theorem that is a direct result of another theorem - Ex. Let n∈ℤ. `n` is even iff `n^2` is even - Proof Sketch: Both directions are contrapositives of the above example --- # 1.8 Proof Methods p2 - Proposition: `[(p->q)^(q->r)] -> (p->r)` is a tautology. - Transitive Law - Suppose we want to show `p1 <-> p2 <-> p3 <-> ... <-> pn` for `n >= 3`. When this is true we say: - "the following are equivalent" (TFAE): 1. `p1` 2. `p2` 3. `p3` n. `pn` - To prove this, it is sufficient to show: `p1 -> p2 -> p3 -> ... -> pn -> p1` - Ex. Let n∈ℤ. Prove TFAE: 1. `5n+4` is even 2. `n^2` is even 3. `n-3` is odd. - Proof: (iii) -> (ii) - Let n∈ℤ s.t. `n-3` is odd - Then, Ǝk∈ℤ s.t. `n-3 = 2k+1` - `n^2` = `(2k+4)^2` = `4k^2 + 16k + 16` = `2(2k^2 + 8k + 8)` - It's **even** since `2k^2 + 8k + 8`∈ℤ - Proof: (ii) -> (i) - Let n∈ℤ s.t. `n^2` is even - We have previously proved that n is even iff n^2 is even. Ǝl∈ℤ s.t. `n = 2l` - Then, `5n+4` = `5(2l)+4` = `10l+4` - It's **even** since `5l+4`∈ℤ - Proof: (i) -> (iii) - Direct Proof: - `5n+4 = 2k` - `n = (2k-4)/5`... too hard, lets use a different strategy - Contrapositive: "If `n-3` is even, then `5n+4` is odd" - Let n∈ℤ s.t. `n-3` is even - Ǝk∈ℤ s.t. `n-3 = 2k` - Then, `n = 2k+3`, so `5n+4` = `5(2k+3) + 4` = `10k+15+4` = `10k+19` = `10k + 18 + 1` = `2(5k+9) + 1` - It's **odd** since `5k+9`∈ℤ ∴ (i), (ii), and (iii) are equivalent. ▣ --- Ex. Prove that for all nonnegative reals, `x` and `y`, `(x+y)/2 >= sqrt(xy)` - The left hand is the "Arithmetic Mean" - The right hand is called the "Geometric Mean - AM - GM Inequality for `n = 2` - Direct Proof is hard - We will use a new method called **Backwards Reasoning** ### Backward Reasoning Show conclusion is **equivalent** to a true statement - Proof: - `(x+y)/2 >= sqrt(xy)` - <-> `((x+y)/2)^2 >= xy` - <-> shows that going from the previous step to this step is reversible - squaring both sides preserves the inequality - <-> `(x^2 + 2xy + y^2)/4 >= xy` - <-> `(x^2 + 2xy + y^2) >= 4xy` - <-> `(x^2 - 2xy + y^2) >= 0` - <-> `(x-y)^2 >= 0` - `a^2 >= 0` is a tautology; it's called "Trivial Inequality" - `≡T` - Since `(x+y)/2 >= sqrt(xy)` is equivalent to a true statement, this inequality is also true - **Note**: For a proof using Backward Reasoning, ensure each step is reversible. Failure to do so could lead to Circular Reasoning --- Ex: Prove `sqrt(2)` is irrational. - Proof: - Assume for the sake of contradiction that `sqrt(2)`∈ℚ - Then, `sqrt(2)` = `a/b` for some a,b∈ℤ, `b!=0` - Suppose `a/b` is written in "lowest terms" - `(sqrt(2))^2 = (a/b)^2` - -> `2 = (a^2)/(b^2)` - -> `2b^2 = a^2` - This means `a^2` is **even** since `b^2`∈ℤ - Recall: "`a` is even iff `a^2` is even" - This implies that `a` is even. - Ǝk∈ℤ s.t. `a=2k` - Substituting `a=2k` into `2b^2 = a^2`, we get `2b^2 = (2k)^2` - -> `2b^2 = 4k^2` - -> `b^2 = 2k^2` - This means `b^2` is even since `k^2`∈ℤ - This implies that `b` is even - However, `a` and `b` being even **contradicts** the assumption that `a/b` is written in lowest terms - As a result, `sqrt(2)` is irrational. ▣ --- [2.1 ->](2.1.md)